(untitled) (Research, Society and Development, 2021)
Objective: to analyze the impact of the Rede Cegonha Strategy in Alagoas on births from 2011 to 2018. Method: ecological study, time series, with secondary data from DATASUS. The data were processed using the Statistical Package for the Social Sciences software. Variables were the mortality coefficient between the years 2011 to 2018, the relationship between the total number of deaths from preventable causes, through multiple regression (p <0.05). Results: the rates understood showed fluctuations, however the Rede Cegonha potentiated the improvements in the indicators of morbidity and mortality. In addition, it was observed that most fetal deaths could be avoided through actions to reduce social inequalities, more high-quality prenatal consultations and to improve the quality of obstetric care aimed at women in the pregnancy-puerperal cycle and to the newborn. Conclusion: it was evident, through the analysis of the indicators, that there is a need for improvement in attention to maternal and child health in Alagoas.